Analisis Sistem Kebijakan Fiskal Modern Dan Islam Serta Fungsinya Dalam Perekonomian: Kebijakan Fiskal - Siti Zainun Nasiqoh (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2022)
Fiscal policy should indeed be applied in the world economy. In the pre-Islamic period, fiscal policy had also been implemented based on the system prevailing at that time. In this study, the researcher wants to explain the problems related to the modern (pre-Islamic) fiscal policy system and the fiscal policy system during the Islamic period. In modern fiscal policy theory, ethics in theory or system reviews are not included in its application. If the preference for good ethical values is applied, it can be used as an effort to prevent various moral crises that attack various government economies which afterward can reduce various kinds of modern economic fiscal results significantly in engineering an economy. The method used in this research is the method of literature review and the data contained in various supporting literature for research and then included in this study. The results of the study explain that modern fiscal policy in general during the Roman, Ancient Egypt, and Yunan empires was under the control of the rulers at that time. The fiscal policy that existed during the Islamic period became a necessity for the state in order to uphold what were the rights of the people, so that it not only served as a need for economic improvement or an increase in the welfare of its people, but fiscal policy was also applied for the implementation of a fair economic distribution mechanism. For Islamic countries, permanent sources of income are ghanimah, fa'i, jizyah, kharaj, and khumus. Zakat is also an independent social assistance tool which is a moral obligation for the rich to help the poor and especially those whose economic conditions tend to be neglected.